Rosa's Einstein : Poems - Givhan, Jennifer (Book collections on Project MUSE., 2019)
"This collection of poetry reevaluates the meaning of borders, Latinx indentity, and immigration narratives through the unlikely amalgamation of physics and fairytale"--Provided by publisher